2012
DOI: 10.4161/cbt.19590
|View full text |Cite
|
Sign up to set email alerts
|

p63 expression correlates with sensitivity to the Eg5 inhibitor AZD4877 in bladder cancer cells

Abstract: Antimitotics such as taxanes are being considered as alternatives to conventional cisplatin-based chemotherapy in patients with bladder cancer, but the molecular determinants of sensitivity or resistance to these agents in bladder cancer cells have not been defined. Here we examined the cytotoxic effects of a novel antimitotic, the Eg5 inhibitor AZD4877, in a molecularly diverse panel of human bladder cancer cell lines. The cells displayed heterogeneous responses to the drug that correlated closely with sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Furthermore, we recently reported that p63 and E-cadherin expression correlated closely with one another in human BC lines and primary tumors (19,20). However, other recent work suggests that normal epithelial stem cells and cancer stem cells from epithelial tissues possess features of EMT (28).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, we recently reported that p63 and E-cadherin expression correlated closely with one another in human BC lines and primary tumors (19,20). However, other recent work suggests that normal epithelial stem cells and cancer stem cells from epithelial tissues possess features of EMT (28).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblotting-Immunoblotting experiments were performed as described previously (20). Primary antibodies used in this study were anti-panp63 (clone 4A4, Santa Cruz Biotechnology, Santa Cruz, CA, catalog no.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations